How apoptosis and epithelial-to-mesenchymal transition are nested in EGFR inhibitors resistance in lung cancer - Garinet, Simon; Didelot, Audrey; Garelli, Elena; Pallier, Karine; Blons, Hélène; Legras, Antoine (Journal of Thoracic Disease, 2019)
Non-small cell lung cancer (NSCLC) is today the first cancer worldwide and represents the first cause of cancer-related death. The identification of EGFR activating mutations and development of specific EGFR inhibitors (EGFRi) such as tyrosine kinase inhibitor (TKI) has changed the management of metastatic NSCLC. However, TKI resistance progressively appeared and EGFR secondary resistance mutation have been identified such as the most frequent T790M (1).